Reported Complications Post Tetralogy of Fallout Repair in One Teaching Center for Cardiac Surgery - Rasool Hussein , Mohammed; Yousif Abed , Noor; Ali Hussein , Ammar; Yousif Abed , Maysam (Hammurabi Journal of Medical Sciences, 2025)
Background: Tetralogy of Fallot (TOF) is a prevalent congenital heart issue with cyanosis. Despite this progress, complications after surgery persists, impacted by variables like surgery timing, approach, and patient attributes. Objectives: investigation TOF repair looking at forecasting complication risk factors. Materials and Methods: In this record-based cross-sectional study, sixty-six Tetralogy of Fallot patients received repairs at the Ibn al-Bitar center between March 2022 and May 2023. Data on patient characteristics, surgery timing, approach, and pre-op conditions were gathered. Post-surgery issues were assessed using predictive modeling techniques. Results: The mean age for surgeries was 2.58 years, and repairs done after age two had a heightened complication risk. The transatrial method was favored in 80.3% of instances due to its advantages in protecting right ventricular function. Key complications comprised arrhythmia (33%), pleural effusion necessitating chest tube insertion (7%), and cardiac arrest (12%). Forecasted complication factors encompassed older repair age, low birth weight, previous palliation, and extracardiac malformations. Conclusions: The research underscores the significance of early TOF repairs and individualized risk evaluation. Results back the transatrial technique for TOF repair and stress the need for thorough monitoring post-surgery, particularly for patients with known risk elements, to enhance TOF management results.